2019
DOI: 10.1038/s41422-019-0251-7
|View full text |Cite
|
Sign up to set email alerts
|

Guiding T lymphopoiesis from pluripotent stem cells by defined transcription factors

Abstract: Achievement of immunocompetent and therapeutic T lymphopoiesis from pluripotent stem cells (PSCs) is a central aim in T cell regenerative medicine. To date, preferentially reconstituting T lymphopoiesis in vivo from PSCs remains a practical challenge. Here we documented that synergistic and transient expression of Runx1 and Hoxa9 restricted in the time window of endothelial-tohematopoietic transition and hematopoietic maturation stages in a PSC differentiation scheme (iR9-PSC) in vitro induced preferential gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 73 publications
1
54
0
Order By: Relevance
“…Runx1 , a member of the Runx (transcription factor associated with runt) family, has been shown to regulate the differentiation of hematopoietic stem cells into mature blood cells ( Cai et al, 2015 ; Guo et al, 2020 ). In addition, Runx1 may play an important role in the phenotype maintain and differentiation of osteoblasts and chondrocyte lineages ( LeBlanc et al, 2015 ; Tang J. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Runx1 , a member of the Runx (transcription factor associated with runt) family, has been shown to regulate the differentiation of hematopoietic stem cells into mature blood cells ( Cai et al, 2015 ; Guo et al, 2020 ). In addition, Runx1 may play an important role in the phenotype maintain and differentiation of osteoblasts and chondrocyte lineages ( LeBlanc et al, 2015 ; Tang J. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we identify that synergistic expression of Runx1, Hoxa9 , and Lhx2 dominantly confers B cell lineage fate on PSC-derived iHPCs and leads to complete B lymphopoiesis in vivo following a differentiation scheme we previously reported (Guo et al, 2020; Wang et al, 2020). The regenerative B (iB) cells, including B-1a, B-1b, FO B, and MZ B subsets, possess a diversity of BCR repertoires similar to their natural B cell counterparts.…”
Section: Introductionmentioning
confidence: 64%
“…pre-HSC isolated from YS and P-Sp also are capable of producing B-1 and B-2 cells (Hadland et al, 2017; Kobayashi et al, 2019), signaling that the B-1 and B-2 cell fate are determined preceding the emergence of definitive HSC. Our group have recently reported that induced hemogenic endothelial progenitors (iHECs), derived from embryonic stem cells with inducible expression of Runx1 and Hoxa9 , can generate induced hematopoietic progenitor cells (iHPCs) preferentially contributing to functional T cells in vivo (Guo et al, 2020). Thus, regeneration of lymphopoiesis from PSCs can be achieved in the absence of regenerative HSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In this protocol, hematopoietic progenitors with thymus-homing abilities were generated by the expression of RUNX1 and HOXA9 at the endothelial-to-hematopoietic transition stage. Upon engraftment, these induced progenitor cells gave rise to T-cells that restore immune surveillance in immune-deficient mice ( 166 ).…”
Section: Immune Cell Programming and Reprogrammingmentioning
confidence: 99%